2020
DOI: 10.3390/nano10091726
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing of Food Packaging Based on Nanocellulose: Current Advances and Challenges

Abstract: Nowadays, environmental pollution due to synthetic polymers represents one of the biggest worldwide challenges. As demonstrated in numerous scientific articles, plant-based nanocellulose (NC) is a biodegradable and nontoxic material whose mechanical, rheological, and gas barrier properties are competitive compared to those of oil-based plastics. However, the sensitivity of NC in humid ambient and lack of thermosealability have proven to be a major obstacle that hinders its breakthrough in various sectors inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(50 citation statements)
references
References 121 publications
0
50
0
Order By: Relevance
“…Scientists and researchers are working on the process of incorporating nanocellulose into food packaging. Nanocellulose has at least one dimension equal to or less than 100 nm and can be divided into cellulose nanofibers and cellulose nanocrystals produced mechanically and chemically, respectively [73]. Cellulose nanocrystals are coated on solid surfaces in multiple layers.…”
Section: Type Of Bio-nanocompositementioning
confidence: 99%
“…Scientists and researchers are working on the process of incorporating nanocellulose into food packaging. Nanocellulose has at least one dimension equal to or less than 100 nm and can be divided into cellulose nanofibers and cellulose nanocrystals produced mechanically and chemically, respectively [73]. Cellulose nanocrystals are coated on solid surfaces in multiple layers.…”
Section: Type Of Bio-nanocompositementioning
confidence: 99%
“…The utilization of nanocomposites for food packaging is a natural welldisposed choice to diminish or supplant the utilization of plastic which is nonbiodegradable [79]. Biodegradability of bundling could be upgraded through the presentation of an inorganic molecule, for example, nanoearth, arranged from regular and adjusted montmorillonite [80].…”
Section: Food Contact Nanomaterials In Foodmentioning
confidence: 99%
“…Sylverud and Stenius (2009) and Spence et al (2010) found grammage values ranging from 17 to 35 g/m², density ranging from 0.8 to 1.1 g/cm³ and porosity from 21 to 48%, studying MFC/NFC films. Grammage, density and porosity of biocomposites are important parameters regarding water degradation, mechanical and barrier properties, mainly aiming applications in packaging or paper coatings (Youssef and El-Sayed 2018;Fotie et al 2020;Nechita and Roman 2020).…”
Section: Physical Properties Of the Filmsmentioning
confidence: 99%